2020
DOI: 10.1137/19m1261766
|View full text |Cite
|
Sign up to set email alerts
|

Books versus Triangles at the Extremal Density

Abstract: A celebrated result of Mantel shows that every graph on n vertices with ⌊n 2 /4⌋ + 1 edges must contain a triangle. A robust version of this result, due to Rademacher, says that there must in fact be at least ⌊n/2⌋ triangles in any such graph. Another strengthening, due to the combined efforts of many authors starting with Erdős, says that any such graph must have an edge which is contained in at least n/6 triangles. Following Mubayi, we study the interplay between these two results, that is, between the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…More generally, we can define graphs G = G n , r ( s ) for which G n , r is the case s = 1 and such that as we increase s from 1, the joint number j r + 1 ( G ) decreases, but the number of copies of K r + 1 increases. It also generalizes the construction that is conjectured by the authors in 26 to be tight for r = 2 and may give an asymptotically tight bound for general r . The graph G has n vertices and a vertex partition into r + 1 parts V 0 , V 1 , … , V r , with V 0 of size s and all the other parts of size nprefix−sr or nprefix−sr.…”
Section: Joints and Cliquessupporting
confidence: 68%
See 3 more Smart Citations
“…More generally, we can define graphs G = G n , r ( s ) for which G n , r is the case s = 1 and such that as we increase s from 1, the joint number j r + 1 ( G ) decreases, but the number of copies of K r + 1 increases. It also generalizes the construction that is conjectured by the authors in 26 to be tight for r = 2 and may give an asymptotically tight bound for general r . The graph G has n vertices and a vertex partition into r + 1 parts V 0 , V 1 , … , V r , with V 0 of size s and all the other parts of size nprefix−sr or nprefix−sr.…”
Section: Joints and Cliquessupporting
confidence: 68%
“…Mubayi 55 showed that t ( n , j ) jumps from quadratic to cubic in n when j goes below the threshold n /4. In 26, we studied this problem in more detail and proposed a precise conjecture that states that if n /6 ≤ j ≤ n /4, then every graph on n vertices with at least ⌊ n 2 /4⌋ edges and no edge in more than j triangles which is not the Turán graph T n , 2 has at least j 2 ( n − 4 j ) triangles. Moreover, we conjectured that equality holds if and only if the graph is S j , n , a blow‐up of the 3‐prism graph, the graph on six vertices which consists of two disjoint triangles with a perfect matching between them, with the parts corresponding to one of the matching edges of size ⌊( n − 4 j )/2⌋ and ⌈( n − 4 j )/2⌉ and the other four parts of size j .…”
Section: Joints and Cliquesmentioning
confidence: 99%
See 2 more Smart Citations